The impacts of climate change on cropland allocation, crop production, output prices and social welfare in Israel: A structural econometric framework. (February 2023) - Kan, Iddo; Reznik, Ami; Kaminski, Jonathan; Kimhi, Ayal
Highlights: We simulate climate change impacts on crop production and food prices under partial equilibrium. The simulation results vary greatly when we allow prices to change as a response to supply changes. Climate changes are projected to benefit Israeli farmers, mostly due to the impact of temperatures. Nearly 20% of the rise in profits is attributed to farmers' adaptation through land reallocation. Abolishing import tariffs has a relatively modest impact on social welfare in Israel. Abstract: We propose a model that simulates climate change impacts on crop production and food prices under partial equilibrium. Our model incorporates a system of Laspeyres price and quantity indices that link structurally estimated community-level produce supply functions to market level demand functions. The supply estimation accounts for corner solutions associated with disaggregate land use observations and is constrained to reproduce aggregate supply data. We use the model to assess climate change impacts in Israel, which protects local agriculture by import tariffs and quotas. The simulation results vary greatly when we allow prices to change as a response to supply changes, highlighting the importance of endogenizing prices in climate change simulations. The results imply that climate changes projected for Israel are expected to be beneficial to farmers, particularly due to the positive impact of the forecasted large temperature rise on field crop production. Fruit outputs are projected to decline, and reduce consumer surplus, but to a lower extent than the increase in total agricultural profits. Nearly 20% of the profit rise is attributed to farmers' adaptation through land reallocation. Adaptation to the projected reduction in precipitation by increasing irrigation is found to be warranted from the farmers' perspective; however, it is not beneficial to society as a whole. Abolishing import tariffs effectively transfers surpluses from producers to consumers, but the impact of this policy on social welfare is relatively modest.